Current Concepts Review: Hallux Rigidus. Issue 2 (7th June 2018) - Anderson, Michael R.; Ho, Bryant S.; Baumhauer, Judith F.
Arthritis of the first metatarsophalangeal (MTP) joint, hallux rigid, is a common and disabling source of foot pain in the adult population. Hallux rigidus is characterized by diseased cartilage and large, periarticular osteophytes that result in a stiff, painful joint. Activity modification, sensible shoes, orthotics, anti-inflammatory medications and occasional intra-articular steroid injections can be attempted to alleviate the discomfort associated with hallux rigidus. A number of surgical options exist for the treatment of recalcitrant hallux rigidus. Cheilectomy is a useful treatment for dorsal impingement pain seen in mild hallux rigidus. A new polyvinyl alcohol hemi-arthroplasty implant has shown promising early and midterm results in the treatment of advanced hallux rigidus; however, arthrodesis of the first MTP joint remains the gold standard treatment for advanced hallux rigidus because of unpredictable outcomes after early-generation joint replacement implants.